2021
DOI: 10.1002/jnr.24934
|View full text |Cite
|
Sign up to set email alerts
|

Is cyclooxygenase‐1 involved in neuroinflammation?

Abstract: Purpose: Reactive microglia are an important hallmark of neuroinflammation. Reactive microglia release various inflammatory mediators, such as cytokines, chemokines, and prostaglandins, which are produced by enzymes like cyclooxygenases (COX). The inducible COX‐2 subtype has been associated with inflammation, whereas the constitutively expressed COX‐1 subtype is generally considered as a housekeeping enzyme. However, recent evidence suggests that COX‐1 can also be upregulated and may play a prominent role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 114 publications
1
25
0
Order By: Relevance
“…19 Furthermore, COX-1 generated prostaglandins also play some role in producing inflammation, and the addition of paracetamol with etoricoxib broadens the efficacy of COX-2 inhibitor etoricoxib more than that of therapeutic dose ibuprofen. 20 In the present study on comparison of safety, it was observed that none of the patients reported any severe adverse reactions in both groups. Mild to moderate adverse drug reactions were reported in 10% of the etoricoxib-treated group and 20% of the ibuprofen-treated group, suggesting that etoricoxib is an overall safer drug than ibuprofen.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…19 Furthermore, COX-1 generated prostaglandins also play some role in producing inflammation, and the addition of paracetamol with etoricoxib broadens the efficacy of COX-2 inhibitor etoricoxib more than that of therapeutic dose ibuprofen. 20 In the present study on comparison of safety, it was observed that none of the patients reported any severe adverse reactions in both groups. Mild to moderate adverse drug reactions were reported in 10% of the etoricoxib-treated group and 20% of the ibuprofen-treated group, suggesting that etoricoxib is an overall safer drug than ibuprofen.…”
Section: Discussionmentioning
confidence: 45%
“…19 Furthermore, COX-1 generated prostaglandins also play some role in producing inflammation, and the addition of paracetamol with etoricoxib broadens the efficacy of COX-2 inhibitor etoricoxib more than that of therapeutic dose ibuprofen. 20…”
Section: Discussionmentioning
confidence: 99%
“…A neuroinflammatory mediator PGE2is produced from PGH2 [ 123 , 124 ]. COX II has more prominent role in the induction of neuroinflammation and COX I is generally considered as the house keeping enzyme [ 125 ].…”
Section: Allicin As a Neuroprotective Agent To Fight Against Neurological Diseasesmentioning
confidence: 99%
“…Scheme 1B summarizes the chemistry used to prepare new honokiol structural analogs (F-I-F-IV)-potential anti-inflammation agents. The key step in the synthesis of these biphenyls was a Suzuki-Miyaura cross-coupling reaction of aryl iodides (3) or bromides (4,11) with aryl boronic compounds. The resulting intermediates (5, 8, 12, 15) were converted into fluoroethoxy compounds (6, 9, 13, 16), which were then deprotected with HCl acid.…”
Section: Chemistrymentioning
confidence: 99%
“…Both known isoforms, COX-1 and COX-2, are expressed in the brain. COX-1 is constitutively expressed in the CNS (as a "house-keeping" enzyme) and is not upregulated by inflammation, although some studies have shown that COX-1 may play a prominent role in neuroinflammation [4]. The inducible type of cyclooxygenase COX-2 is rapidly and dramatically overexpressed under inflammatory conditions and, therefore, is one of the most attractive molecular targets for PET imaging of neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%